Is effective coordination the key to sustainable performance? A probe into integrated e-agri supply chains in India - Singh, Vinay; Agrawal, Shivani; Kumar, Sachin (International journal of productivity and performance management, 2025)
PurposeThe study aims to assess how e-agri supply chain coordination (SCC), supply chain integration (SCI) and competitive capabilities (COC) impact both market performance (MO) and operational performance (OP). It particularly emphasizes the critical role of information flow for the benefit of farmers, intermediaries and end-consumers, shedding light on the broader implications of these factors within the agricultural supply chain.Design/methodology/approachData are collected online from farmers, intermediaries engaged in buying/supplying agri-products and consumers using a semi-structured questionnaire of 25 items adapted from the extant literature measuring SCC, SCI, COC, OP and MP. The survey instrument is validated for its reliability, convergent and discriminant validity tests. Purposive and convenient sampling is used for data collection. Finally, 280 responses were analyzed using SEM to conclude the study.FindingsFindings underscore information flow’s significance in the e-agri supply chain, addressing various stakeholders’ needs. Technical excellence, featuring robust transaction capabilities and cost-effective maintenance is pivotal. Enhanced supply chain coordination fosters integration and efficient information sharing, enhancing agricultural market performance and sectoral efficiency.Research limitations/implicationsThe study explores technology adoption, understands information flow and coordination impact, enhances efficiencies, empowers farmers and promotes transparency, sustainability and consumer benefits.Practical implicationsThe study promotes efficient information flow, digital adoption, collaborative planning, tech investment and enhanced responsiveness for agricultural sector managers.Social implicationsThe study bridges the rural-urban divide, empowering farmers, providing fair pricing, sustainable practices, transparency, informed consumers, responsible consumption and income distribution.Originality/valueThe novelty of this study lies in its comprehensive information flow study, new theoretical model and e-agri-specific sub-constructs that define coordination and integration, aiding efficiency and competitiveness.